2006
DOI: 10.1103/physrevlett.97.085501
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Ion Channeling inAlInN/GaNBilayers: Determination of the Strain State

Abstract: Monte Carlo simulations of anomalous ion channeling in near-lattice-matched AlInN/GaN bilayers allow an accurate determination of the strain state of AlInN by Rutherford backscattering or channeling. Although these strain estimates agree well with x-ray diffraction (XRD) results, XRD composition estimates are shown to have limited accuracy, due to a possible deviation from Vegard's law, which we quantify for this alloy. As the InN fraction increases from 13% to 19%, the strain in AlInN films changes from tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
120
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 137 publications
(130 citation statements)
references
References 18 publications
8
120
2
Order By: Relevance
“…In our experience WDX provides composition data of similar accuracy to that from Rutherford backscattering spectrometry ͑RBS͒. 10,11 Advantages of WDX over RBS include the higher lateral spatial resolution ͑down to 100 nm͒ and the possibility of simultaneous CL spectroscopy, while RBS has much better depth resolution. These methods have some advantages compared to measurement of AlInGaN composition using standard x-ray diffraction, which can be complicated by the lack of a unique solution for the quaternary system.…”
Section: Introductionmentioning
confidence: 94%
“…In our experience WDX provides composition data of similar accuracy to that from Rutherford backscattering spectrometry ͑RBS͒. 10,11 Advantages of WDX over RBS include the higher lateral spatial resolution ͑down to 100 nm͒ and the possibility of simultaneous CL spectroscopy, while RBS has much better depth resolution. These methods have some advantages compared to measurement of AlInGaN composition using standard x-ray diffraction, which can be complicated by the lack of a unique solution for the quaternary system.…”
Section: Introductionmentioning
confidence: 94%
“…This ultimately acts as a sacrificial layer in a selective wet etching step, 11 but also allows endpoint detection during plasma etch steps which precede this. The sacrificial Al 0.83 In 0.17 N is lattice matched to GaN, 3,12 and the high quality of GaN grown above such a layer has recently been confirmed by spectroscopic and structural characterization. 13 The refractive index contrast between Al 0.83 In 0.17 N and GaN is also valuable in facilitating in situ reflectometry during epitaxy on FS-GaN.…”
mentioning
confidence: 90%
“…The potential of RBS/C has been proved on several semiconductor heterostructures ͑HSs͒, where elastic strain is a main issue affecting band gap and carrier density. 3 However, this kind of RBS/C studies has shown anomalous behaviors in the angular scans ͑asymmetries or double dips͒, [4][5][6] which decrease the accuracy in the strain determination. The origin of these anomalous channeling processes has been clearly linked to the presence of steering effects ͑deviation of the projectile due to electrostatic interactions with the target atoms͒ at the interface of the junction.…”
mentioning
confidence: 99%
“…The origin of these anomalous channeling processes has been clearly linked to the presence of steering effects ͑deviation of the projectile due to electrostatic interactions with the target atoms͒ at the interface of the junction. 5 The thickness of the layer and the strain state strongly influence this behavior since the steering operates when ⌬ is smaller or comparable to the critical angle for channeling ͑ 1 ͒. 7 In some cases, this error can be corrected by additional Monte Carlo ͑MC͒ simulations, 5,7 but in others this approach is not sufficient.…”
mentioning
confidence: 99%
See 1 more Smart Citation